Analysis of Total Productive Maintenance (Tpm) Implementation Using Overall Equipment Effectiveness (Oee) And Autonomous Maintenance Methods in The Universal Pack 6 Machine - Irawan, Agus; Wahidjul, Sofyan; Abdulwahid, Azhar; Ahfadan, Ganjar; M.T. , Yani Iriani Dra (International Journal of Psychosocial Rehabilitation, 2020)
The quality of products from an industry cannot be separated from one indication of the role of equipment. Equipment is one important factor that must be maintained with the implementation of maintenance and repairs. PT. XYZ is a company engaged in the manufacture of nutritional drinks. Problem that can be found at PT. XYZ is the number of breakdowns that occur on the Universal Pack 6 line 7 machine reaching 13.40% of production time. This results in a reduction in the maximum amount of production and results in a lack of effectiveness index value. One of the measurement tools to increase productivity is the measurement of Total Productive Maintenance (TPM) with the calculation of Overall Equipment Effectiveness (OEE). OEE is a systematic method to make improvements in the effectiveness level of the machine or equipment process. This study aims to calculate the OEE value of the Universal Pack 6 line 7 machine, analyzing the OEE value, and determining corrective action with the Autonomous Maintenance approach. Autonomous Maintenance is one of the pillars of TPM (Total Productive Maintenance) by using the principle of independent maintenance by machine operators to increase the knowledge, skills, and responsibilities of production operators related to the machine so that productivity will increase as a whole. The study consists of an activity of real productivity data recapitulation, determining availability rate, performance rate, and quality statistic. Based on the results of the current calculation, it obtains the availability value of 79.16%, performance of 78.26% and quality of 98.71%, while the average OEE value for Universal Pack 6 line 7 machine is 61.15%, this shows that the machine performance is still below standard and corrective action must be taken. To increase the OEE value in Universal Pack 6 line 7, the proposed improvement is to conduct Preventive Maintenance periodically to maintain machine performance, training for operators and supervising operators. After the improvement is made, the availability value of 89.82%, the performance of 78.26%, the quality of 99.35% and the average OEE value of 69.83% (there is an increase of 8.68%.)